Persepsi Civitas Akademika STAIN Manado Tentang Kesyariahan Produk Perbankan Berasaskan Islam - Syarifuddin Syarifuddin (IAIN Manado, 2018)
This research ains to identity the perception of the civitas academica of (STAIN) Manado on the Syariah base of Islamic Banking Products. The interaction between betwen civitas academica of STAIN Manado and Islamic banks (Bank of Muamalat Indonesia, Branch Manado), through Koperasi (Cooperation) STAIN Manado, has inded, brought understanding between clients and bank. Therefore, they dealt on murabaha and mudharabah contracts. The method used is a descriptive- qualitative one with a case study. Interview is the technique used for data collection The research finding Shows that some for civitas academica do not completely understand the Concep of the profit sharing system. So that, they consider the Shariah banks are less the the conventional ones in terms of Quality and Quantity.Key word; Perception, product, Sharia Banking